2020
DOI: 10.36351/pjo.v36i1.903
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Of Pseudophakic Glaucoma In A Tertiary Care Hospital Of Pakistan

Abstract: Purpose:  To evaluate the frequency, causes and management of pseudophakic glaucoma among the pseudophakic patients presenting in a tertiary care hospital of Pakistan. Study Design:  Descriptive cross sectional study. Place and Duration of Study:  Department of Ophthalmology, Abbasi Shaheed Hospital, Pakistan, from August 2017 to June 2018. Material and Methods:  Adult patients between 50 to 70 years of age with pseudophakic glaucoma were included in the study by non-probability convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In this study, the spectrum of ocular disease in children between the age of 0 and 36 months presenting to an Australian tertiary paediatric hospital was evaluated. There have been analogous studies examining the spectrum of ocular disease at a paediatric tertiary hospital in Africa, the Middle East and India, albeit with broader age ranges and smaller sample sizes 5–14 . To our knowledge, this is the first study of its kind in Australia and more widely in the developed world.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In this study, the spectrum of ocular disease in children between the age of 0 and 36 months presenting to an Australian tertiary paediatric hospital was evaluated. There have been analogous studies examining the spectrum of ocular disease at a paediatric tertiary hospital in Africa, the Middle East and India, albeit with broader age ranges and smaller sample sizes 5–14 . To our knowledge, this is the first study of its kind in Australia and more widely in the developed world.…”
Section: Discussionmentioning
confidence: 92%
“…There have been analogous studies examining the spectrum of ocular disease at a paediatric tertiary hospital in Africa, the Middle East and India, albeit with broader age ranges and smaller sample sizes. [5][6][7][8][9][10][11][12][13][14] To our knowledge, this is the first study of its kind in Australia and more widely in the developed world. Strikingly, there is an absence of studies structurally analogous to ours from the European, Pacific or American regions.…”
Section: Site Of Primary Abnormalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Many of previous studies 18,19 demonstrated that the incidence of glaucoma was higher in patients who received ECCE as compared to phacoemulsification. The difference was reported statistically significant and this showed similarity to the present study.…”
Section: Discussionmentioning
confidence: 98%